2002
DOI: 10.1073/pnas.052707099
|View full text |Cite
|
Sign up to set email alerts
|

The peroxisome proliferator-activated receptor δ, an integrator of transcriptional repression and nuclear receptor signaling

Abstract: The three PPAR (peroxisome proliferator-activated receptor) isoforms are critical regulators of lipid homeostasis by controlling the balance between the burning and storage of long chain fatty acids. Whereas PPAR␣ and PPAR␥ have been studied extensively, the function of PPAR␦ remains the most elusive. Intriguingly, in cotransfection experiments, PPAR␦ is a potent inhibitor of ligandinduced transcriptional activity of PPAR␣ and PPAR␥. This inhibition is achieved, in part, by binding of PPAR␦ to a peroxisome pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
223
2
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 290 publications
(242 citation statements)
references
References 38 publications
15
223
2
2
Order By: Relevance
“…Taken together, these results indicate that gemfibrozil stimulates the expression of myelin genes via PPAR-␤ but not via either PPAR-␣ or PPAR-␥. Our results are consistent with published reports that demonstrate reduced myelination of the corpus callosum in PPAR-␤-null mice and suggest a role of PPAR-␤ in oligodendroglial lipid metabolism and myelinogenesis (41,42).…”
Section: Discussionsupporting
confidence: 93%
“…Taken together, these results indicate that gemfibrozil stimulates the expression of myelin genes via PPAR-␤ but not via either PPAR-␣ or PPAR-␥. Our results are consistent with published reports that demonstrate reduced myelination of the corpus callosum in PPAR-␤-null mice and suggest a role of PPAR-␤ in oligodendroglial lipid metabolism and myelinogenesis (41,42).…”
Section: Discussionsupporting
confidence: 93%
“…Although not examined in the current study, there is evidence that PPAR␤/␦ can also modulate gene expression by repressing transcription. 48 Thus, it remains possible that PPAR␤/␦ protects against liver toxicity by repressing expression of TWEAK receptor, which in turn reduces NF-B activity. Collectively, results from the current present studies suggest that PPAR␤/␦ could protect against liver toxicity by directly interacting with NF-B or by repressing TWEAK receptor expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, in salmon at least, it appears that there are multiple genes for PPARβ isoforms (Leaver, personal communication) and since there is only one PPARβ gene in mammals, there yet may be some divergence in the functions of PPARs between fish and mammals. Interestingly, although PPARβ is probably the least well studied PPAR isoform, it has recently been shown that PPARβ may function as a negative regulator of PPARα and PPARγ function by competing for binding at gene regulatory elements and then recruiting proteins involved in depressing transcriptional activity (Shi et al, 2002). (Kawashima et al, 1990;Gronn et al, 1992;Alegret et al, 1995) and clofibrate has been shown to increase the desaturation of 20:5n-3 in rainbow trout (Tocher and Sargent, 1993).…”
Section: Transcriptional Control Of Lipid Homeostasismentioning
confidence: 99%